Definitions of risk - Instefjord, Norvald (Henry Stewart Talks, 2007)
Distributional properties of risk, Variance, Risk aversion and variance aversion, First order stochastic dominance, Second order stochastic dominance, Axiomatic approach to risk measures, Risk as a choice variable, Acceptable and non-acceptable risk, Single-dimensional risk measures, Risk measure and risk capital, Coherent risk measurers, Value-at-Risk (VaR) is not coherent, TailVaR and worst conditional expectations, Rothschild/Stiglitz increasing risk, Conclusions: risk definition depends on context and purpose
Archived at 2022/04/04